Comparative study on drivers' eye movement characteristics and psycho-physiological reactions at tunnel entrances in plain and high-altitude areas: A pilot study. (April 2022) - Yan, Guanfeng; Wang, Mingnian; Qin, Pengcheng; Yan, Tao; Bao, Yifan; Wang, Xu
Highlights: Characteristics of typical road tunnels in plain and high-altitude areas. Eye movement characteristics at tunnel entrances in plain and high-altitude areas. Psycho-physiological reactions at tunnel entrances in plain and high-altitude areas. Measures drivers would adopt to cope with the danger in high-altitude areas. Abstract: The safety of drivers when driving through road tunnel entrances is a major concern for researchers. Most studies on this topic have mainly focused on tunnels in plain areas. However, there are many road tunnels in high-altitude areas where environmental and tunnel design parameters, which may influence driver behavior, change with elevation. Therefore, it is necessary to explore drivers' eye movement characteristics and psycho-physiological reactions at tunnel entrances in plain and high-altitude areas respectively. In this study, a series of driving experiments were conducted at two typical road tunnel entrances in plain and high-altitude areas through eye movement measurements, physiological tests, and a questionnaire to explore the drivers' eye movement characteristics and psycho-physiological reactions. The results show that the pupil size of drivers is mainly related to the ambient illuminance, and the change in illuminance at tunnel entrances in high-altitude areas is greater due to fewer lights, resulting in a greater change of rate in pupil diameter. Drivers pay more attention to their surroundings in high-altitude areas due to the complex driving environment outside the tunnel; inside the tunnel, drivers focus on the central sight area where the opposite vehicle may appear in high-altitude areas and are more attentive to the road ahead because of greater traffic volume in plain areas. Lower oxygen content and a sharper decrease in illumination can hinder the information-processing ability of drivers; therefore, the fixation duration inside the tunnel is greater in high-altitude areas. Drivers believe that driving through tunnel entrances in high-altitude areas is more dangerous, which prompts them to adapt their driving behavior such as lowering the vehicle speed, paying more attention, and increasing the following distance.